2020
DOI: 10.1007/s40199-019-00320-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of phytoestrogens in inducing cell death mediated by decreasing Annexin A1 in Annexin A1-knockdown leukemia cells

Abstract: Background Phytoestrogens are plant compounds that are structurally similar to estrogen and that possess anti-cancer properties. Previous studies have reported that coumestrol, daidzein and genistein could induce cell death by reducing Annexin A1 protein in leukemic cell lines. Annexin A1 (ANXA1) is involved in cell progression, metastasis, and apoptosis in several types of cancer cells. The present study sought to investigate if the effects of phytoestrogens on apoptosis, cell cycle arrest and phagocytosis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…This result suggested that phytoestrogen compounds had strong killing effect toward leukemic cells and may be safe for normal cells, since higher percentage of apoptosis was possibly contributed to by a characteristic of cancer cells, which was more sensitive to the phytoestrogens as compared to normal cells. These results were in line with a previous study, where the same phytoestrogens induced apoptosis and cell cycle arrest in Annexin A1 (ANXA1)-knockdown leukemia cells [15]. Sabran et al reported that ANXA1 level was higher in leukemic cells compared to PBMC [16].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result suggested that phytoestrogen compounds had strong killing effect toward leukemic cells and may be safe for normal cells, since higher percentage of apoptosis was possibly contributed to by a characteristic of cancer cells, which was more sensitive to the phytoestrogens as compared to normal cells. These results were in line with a previous study, where the same phytoestrogens induced apoptosis and cell cycle arrest in Annexin A1 (ANXA1)-knockdown leukemia cells [15]. Sabran et al reported that ANXA1 level was higher in leukemic cells compared to PBMC [16].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, when ANXA1 in leukemic cells was knocked down, the cells exhibited apoptosis. Thus, phytoestrogen induced apoptosis might be mediated by ANXA1 [15]. These results were reinforced by Pignata et al, in which the study stated that apoptosis in normal cells might be due to a lengthy incubation period that could stimulate activation of cell death via initiation of mature T cells [17].…”
Section: Discussionmentioning
confidence: 90%
“…However, placebo effect shows no changes in isoflavones and placebo group which shows more research is needed (21). Another study suggests that soy intake in early life will help you in protection (26).…”
Section: Breast Cancer and Phytoestrogenmentioning
confidence: 99%
“…In AML, preclinical studies have shown that it induces cell death in a variety of leukemia cell lines and that a genistein-rich diet improves survival in leukemia-bearing mice [78]. Mechanistically, it has been shown to cause G2/M cell cycle arrest, increase reactive oxygen species (ROS) generation, cause mitochondrial membrane polarization, reduce protein synthesis through inhibition of mTOR, and change the BAX/Bcl2 ratio, leading to apoptosis [79][80][81]. Additionally, genistein and other polyphenols can enhance the anti-AML action of the glycolytic inhibitors 2-deoxy-D-glucose and lonidamine by inhibiting the compensatory activation of protein kinases such as Akt and extracellular signal-regulated kinase (ERK) [82].…”
Section: Genisteinmentioning
confidence: 99%